Appropriate and Efficient Technology System Approach in Product Design to Reduce Musculoskeletal Disorders - Zulkarnaen; Marali Banjarnahor; Rudi Salam (International Journal of Innovation in Enterprise System, 2024)
The process of planting corn still uses the traditional method of using wood that is sharpened at theend while holding a bag containing corn seeds, the process of planting corn is carried out by bendingthe body continuously, this process is carried out minimum two workers. This process causesperformance to be not optimal, besides that the work process will accelerate fatigue and cause manycomplaints, pain, and injuries. This study aims to measure anthropometric data of standing shoulderheight, standing elbow height, forearm length, hand width, and hand grip diameter. The results ofthese measurements are then used to design products for these farmers. This measurement alsoincludes a Nordic Body Map (NBM) questionnaire to determine of pain in the corn planting process.The subjects in this study were 30 people, after calculation and data processing, the right size for theproduct design is obtained which consists of a tool height of 140 cm, a handle height of 105 cm, adiameter of grip 5 cm, grip length of 9 cm, an operator distance with a tool of 45 cm, then the toolassembly process and testing process will be carried out.